2022
DOI: 10.3390/ph15080924
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of Antimicrobial Photodynamic Therapy in Residual Periodontal Pockets during the Maintenance Phase

Abstract: Antimicrobial photodynamic therapy (a-PDT) in combination with scaling root planing (SRP) is more effective at improving periodontal status than SRP alone. However, the effectiveness of a-PDT in combination with irrigation for patients undergoing periodontal maintenance has not been clarified. This study evaluated the efficacy and safety of a-PDT in the maintenance phase. Patients who had multiple sites with bleeding on probing (BOP) and periodontal probing depth (PPD) of 4–6 mm in the maintenance phase were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The photosensitizer and the optical fiber placed in the periodontal and peri-implant pockets could reach the root or implant surface before activation with the laser light [ 50 ]. The big amount of randomized controlled clinical trials has shown that a-PDT and scale root planning (SRP) can cause significant enhancements in PPD and clinical attachment level than SRP alone [ 32 , 33 , 51 , 52 , 53 ]. The aPDT properties against bacteria and virus agents could be realized with different lasers and photosensitive substances.…”
Section: Discussionmentioning
confidence: 99%
“…The photosensitizer and the optical fiber placed in the periodontal and peri-implant pockets could reach the root or implant surface before activation with the laser light [ 50 ]. The big amount of randomized controlled clinical trials has shown that a-PDT and scale root planning (SRP) can cause significant enhancements in PPD and clinical attachment level than SRP alone [ 32 , 33 , 51 , 52 , 53 ]. The aPDT properties against bacteria and virus agents could be realized with different lasers and photosensitive substances.…”
Section: Discussionmentioning
confidence: 99%
“…with periodontitis. 89 Yamashita et al 90 showed PDT-irrigation combination therapy with irrigation alone in maintenance patients and found that BOP significantly decreased from 100% to 33% in the PDT-irrigation group. Many studies showed that PDT could significantly reduce PPD and gain more CAL and SBI than SRP alone.…”
Section: Clinical Effects Of the Pdt-assisted Srpmentioning
confidence: 99%
“…showed that multiple applications of PDT significantly improved bleeding on probing (BOP) compared with SRP alone, which also can be seen among geriatric patients with periodontitis 89 . Yamashita et al 90 . showed PDT‐irrigation combination therapy with irrigation alone in maintenance patients and found that BOP significantly decreased from 100% to 33% in the PDT‐irrigation group.…”
Section: Clinical Effect Of Pdt In the Treatment Of Periodontitismentioning
confidence: 99%
“…On the other hand, there is limited proof that antibacterial PDT is beneficial during the periodontal maintenance phase. 20 Periodontal diseases have been successfully treated with PDT. Due to the difficulties of accessing confined spaces, mechanical removal of gold standard biofilm in the therapeutic management of periodontal diseases is impaired in difficult-toaccess locations.…”
Section: Evidence From Literaturementioning
confidence: 99%